SOLVING THE STUDENTS’ SPEAKING PROBLEM IN DELIVERING ENGLISH PRESENTATION THROUGH 3-P TECHNIQUE - Nadif Ulfia (IKIP PGRI Bojonegoro, 2017)
Abstract: Solving the Students’ Speaking Problem in Delivering English Presentation Through 3-P Technique. The aims of this study were to (1) identify whether and to what extent 3-P Technique can improve the students’ speaking competence in delivering presentation;(2) describe the teaching and learning when 3-P technique is implemented in English class. This research was conducted at the eleventh grades of MAN 1 Bojonegoro. The subjects of the research were the teacher and the students in the academic year 2016/2017. This study applied 3 cycle action research. In collecting the data, the researcher used observations through field notes, video recording, questionnaire and interview. To analyze the quantitative data, the researcher applied descriptive statistics. Besides, to analyze qualitative data, the researcher applied constant comparative method as suggested by Garner. The findings shows that: (1) 3-P Technique can improve students’ speaking competence in delivering presentation in terms of students achievement, fluency, pronunciation, ability to express their opinions, arguments, and ideas using appropriate vocabulary and grammatical form, using appropriate body language, voice control, gesture, and eye contact; and (2) 3-P technique can improve classroom situation in terms of increasing students’ motivation and participation, creating live teaching atmosphere, and increasing teacher motivation.Key words: Speaking, 3 P technique, Action researchAbstrak: Memecahkan Masalah Keterampilan Berbicara Siswa dalam Menyampaikan Presentasi Berbahasa Inggris Melalui Teknik 3-P. Tujuan dari penelitian ini adalah untuk (1) mengidentifikasi dan mengetahui sejauh mana teknik 3-P dapat meningkatkan kemampuan berbicara para siswa dalam menyampaikan sebuah presentasi; (2) mendeskripsikan kegiatan pembelajaran dalam penerapan teknik 3-P dalam pembelajaran Bahasa Inggris. Penelitian ini dilakukan pada kelas sebelas MAN 1 Bojonegoro. Subyek penelitian ini adalah guru dan para siswa pata tahun pelajaran 2016/2017. Penelitian ini menggunakan 3 siklus penelitian tindakan kelas. Dalam mengumpulan data, peneliti menggunakan teknik observasi melalui catatan lapangan, rekaman video, kuesioner dan wawancara. Untuk menganalisis data kuntitatif, peneliti menggunakan teknik deskiptif statistic, sedangkn untuk menganalisis data kulitatif, peneliti menggunakan metode konstan komparatif oleh Garner. Hasil penelitian menunjukkan bahwa: (1) teknik 3-P dapat meningkatkan kemampuan siswa dalam berbicara khususnya dalam melakukan sebuah presentasi dalam hal prestasi belajar siswa, kefasihan, pengucapan, dan kemampuan untuk mengemukakan opini, argumentasi dan ide menggunakan kosakata yang tepat, susunan gramatikal, dan bahasa tubah yang tepat, control suara, kontk mata. (2) teknik 3-P dpat meningkatkan kondisi kelas dalam hal meningkatkan motivasi dan partisispasi siswa, menciptakan atmosfir kelas yang lebih aktif, dan meningkatkan motivasi guru dalam mengajar.Kata kunci: Berbicara, Teknik 3-P, Penelitian tindkan kelas.